2022
DOI: 10.3389/fimmu.2022.865643
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and Clinicopathological Significance of Systemic Immune-Inflammation Index in Bladder Cancer

Abstract: BackgroundSystemic immune-inflammation index (SII) has recently emerged as a biomarker for the prognosis of a variety of malignant tumors. However, the role of SII in bladder cancer (BC) remains unclear. To this end, we performed a pooled analysis to investigate the prognostic value of preoperative SII in patients with BC.MethodsA comprehensive search of electronic databases (PubMed/Medline, Web of Science, Scopus, and Cochrane Central Register of Controlled Trials) was conducted to determine the eligible stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Also, a previous meta‐analysis showed that a high SII was correlated with poor OS 59 and a higher SII implies higher platelet/neutrophil and/or lower lymphocyte counts. 54 , 60 Thus, a higher SII indirectly represents a deficiency of immune function and increased tumor aggressiveness in patients with thymoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a previous meta‐analysis showed that a high SII was correlated with poor OS 59 and a higher SII implies higher platelet/neutrophil and/or lower lymphocyte counts. 54 , 60 Thus, a higher SII indirectly represents a deficiency of immune function and increased tumor aggressiveness in patients with thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…47 In this study, SII was used to predict OS and compared to PLR and NLR, SII effectively integrated blood-based markers of inflammation instead of only calculating the ratio of the two types of immune cells, therefore has better predictive and prognostic capabilities. 54 SII has been used for various tumors such as lung adenocarcinoma, 55 hepatocellular carcinoma, 56 oesophagal squamous cell carcinoma (ESCC) and cervical cancer, and is superior to PLR and NLR as a predictive biomarker in ESCC and cervical cancer. 57,58 This was also the case in our study.…”
Section: Factorsmentioning
confidence: 99%
“…In the subgroups of sex, age, BMI and diabetes, there is a stable nonlinear association. SII indicators are usually used to predict the prognosis of cancer patients [13][14][15][16] and patients with CVD [17][18][19][20], and without exception, higher SII levels are associated with poor prognosis, and there has never been a nonlinear association between SII and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…SII was calculated according to the counts of lymphocytes, neutrophils and platelets. SII usually serves as a prognostic factor for cancer patients [14][15][16] and patients with cardiovascular disease (CVD) [17][18][19][20]. Only Xu et al [21] investigated the association between various immune-inflammatory indices, including SII, and hypertension using NHANSE patients' data from 1999 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…A number of immune in ammation markers have been evaluated for their potential as tumor prognostic biomarkers, such as systemic immune in ammation index(SII), C-reactive protein/albumin ratio(CAR), brinogen with neutrophil-lymphocyte ratio (F-NLR) and prognostic nutritional index (PNI) [10,11,12,13]. However, due to limitations, these indicators are not widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%